Diaspora weavers: Collective memory and identity of Pagatan Weaving South Kalimantan - Hidayah, Sri; Saptandari, Pinky; Arimbi, Diah Ariani (Jurnal Sosiologi Dialektika, 2024)
This study aims to analyze more deeply the collective memory of Bugis weaver community in Pagatan through the form of creating weavers’ works that are not only a residue of the past, but also as a representation of the memories collected for their sustainable cultural identity. This research is based on Bugis community in Pagatan as an illustration of diaspora community that continues to carry out its traditions from their ancestors. This research uses qualitative methods, namely observation, in-depth interviews, and FGD (Focus Group Discussion). The purposive technique is carried out to identify informants that have been determined based on the research objectives. This study was analyzed using Maurice Halbwachs’ collective memory theory which said that collective memory embedded in the collective mind of the community forms the story of the past as part of the social identity of the community. This research finds that the systematic sequence of the past is like a collection of threads that are intertwined at a certain time, woven into one and cannot be separated from the present point of view. This research concludes that weavers are also able to manage its collective memory by expressing it through forms of Pagatan Weaving motifs as a strategy to survive its identity.